Analysis of Quality Level of Outpatients in Puskesmas Baktiya Using Fuzzy-Servqual Method (Service Quality). Issue 1 (December 2020) - Bakhtiar,; Zakaria, Muhammad; Anshar, Khairul; Wahyuni, Fitri
Abstract: Puskesmas Baktiya is a company engaged in central of public health service services related to the patient. Thus it is necessary to improve the quality of services provided so that customers feel comfortable and satisfied, and need a method to measure the quality of Pusksmas Baktiya. The data collection steps were conducted by observing and distributing questionnaires from several criteria. The criteria are obtained through interviews and literature study. The method used to measure the quality of service using Fuzzy-Servqual. The research instrument used questionnaires with a total sample of 40 respondents, ie outpatients Puskesmas Baktiya. The results of data processing, obtained that the value of fuzzy-servqual per criteria as a whol has a low value so that Puskesmas Baktiya needs to make improvements. It also shows that customer expectations are not yet in line with the perceptions of the services they receive. With these results the management of Puskesmas Baktiya need to immediately improve the quality of service to attract patients. Patient waiting time for service to doctor's office (after registration) and patient waiting time for drug taking (after service in check room).